2015
DOI: 10.1021/acs.jpca.5b00567
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Hydrosilylation of Unsaturated Carbon–Heteroatom (C═O, C═N) Bonds by Rhenium(V)–Dioxo Complexes

Abstract: The hydrosilylation of unsaturated carbon-heteroatom (C═O, C═N) bonds catalyzed by high-valent rhenium(V)-dioxo complex ReO2I(PPh3)2 (1) were studied computationally to determine the underlying mechanism. Our calculations revealed that the ionic outer-sphere pathway in which the organic substrate attacks the Si center in an η(1)-silane rhenium adduct to prompt the heterolytic cleavage of the Si-H bond is the most energetically favorable process for rhenium(V)-dioxo complex 1 catalyzed hydrosilylation of imines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 109 publications
0
10
0
1
Order By: Relevance
“…These data suggest that the most favorable pathway does not require aldehyde insertion into the Re-H bond. Furthermore, these experiments would also discard the ionic outer-sphere mechanism proposed by Wei's group (Scheme 13) [17]. Therefore, the [2+2]-addition reaction of the hydrosilane to complex (by substitution of a phosphine ligand), followed by attack of the R3Si + from the η 2silane to generate a cationic silylether O-bound to rhenium that affords the hydrosilylation product by recombination with the hydride ligand.…”
Section: Nonhydride Mechanismsmentioning
confidence: 98%
See 1 more Smart Citation
“…These data suggest that the most favorable pathway does not require aldehyde insertion into the Re-H bond. Furthermore, these experiments would also discard the ionic outer-sphere mechanism proposed by Wei's group (Scheme 13) [17]. Therefore, the [2+2]-addition reaction of the hydrosilane to complex (by substitution of a phosphine ligand), followed by attack of the R3Si + from the η 2silane to generate a cationic silylether O-bound to rhenium that affords the hydrosilylation product by recombination with the hydride ligand.…”
Section: Nonhydride Mechanismsmentioning
confidence: 98%
“…In contrast to the mechanistic studies by Toste et al, which indicate an oxo ligandassisted mechanism for catalyst 5, recent DFT studies have postulated that an ionic outer-sphere pathway (Scheme 13) may compete with the [2+2] addition mechanism in the case of carbonyl compounds. Furthermore, in the case of imines, the outersphere pathway would prevail [17].…”
Section: Scheme 11mentioning
confidence: 99%
“…[68] One study examined the electrophilic Si-H σ-complex pathway and the Toste mechanistic proposal for hydrosilation of imines and aldehydes using catalyst 23. [68a] The authors concluded that the electrophilic Si-H activation pathway involving an η 1 -H-SiR3 complex is most favorable for the hydrosilation of imines, while the Toste proposal is slightly more favorable for benzaldehyde as the substrate.…”
Section: Electrophilic Si-h Activation By Rheniummentioning
confidence: 99%
“…These mechanisms are different, depending on the hydrosilylation substrate and the catalyst, such as the central metal, its oxidation state, and the ligands. Some of these proposed mechanisms have been supported by theoretical studies …”
Section: Introductionmentioning
confidence: 73%